CD19+ B cell depletion: a novel strategy to alleviate ischemic stroke damage - Xu, Yu; Peng, Jing; Yan, Yizhong; Gao, Min; Zang, HongJing; Cheng, Lamei; Zhou, Yu (Frontiers in Immunology, 2025)
BackgroundIschemic stroke, accounting for approximately 80% of all stroke cases, is a major public health challenge and a leading cause of death and disability worldwide. Current treatments primarily involve thrombolytic therapy, limited to a 4.5-hour window due to the risk of complications, underscoring the need for new therapeutic targets. Systemic inflammation plays a critical role in stroke progression, with immune cells infiltrating the brain and exacerbating damage. B cells, in particular, have been implicated in stroke pathogenesis, although their exact role remains contentious. This study examines anti-CD19 antibody (aCD19 Ab) treatment in a stroke model to determine if CD19+ B cell depletion can reduce infarct size and alleviate inflammation.ResultsThis study investigated whether temporary inhibition of B-cell activity using an aCD19 Ab could alleviate ischemic brain injury in a stroke mouse model by regulating cerebral and systemic immune reactions. Mice subjected to middle cerebral artery occlusion (MCAO) exhibited significant reductions in infarct size and brain edema, prolonged post-MCAO survival, and improved behavioral outcomes following aCD19 Ab treatment. Transmission electron microscopy (TEM) and Computed Tomography Angiography (CTA) results revealed a reduction in microvascular endothelial edema, decreased mitochondrial damage in neurons, reduced neuronal apoptosis, and a favorable reconstruction of the cerebral vascular network. Additionally, B cell inhibition reduced pro-inflammatory cytokines and immune cells in the brain and peripheral circulation. The immune response alterations observed in the MCAO/R group were consistent with the trends indicated by stroke patient data.ConclusionsTemporary inhibition of B-cell activity via aCD19 antibody injection alleviated ischemic brain injury in a mouse model of stroke by suppressing systemic immune reactions. Changes in immune cells within the meninges may play a role, and further investigation is needed to understand the mechanisms involved. These findings suggest that cerebral and systemic immune responses contribute to the pathogenesis of ischemic stroke, and temporary B cell depletion may represent a potential therapeutic target for stroke therapy.